Bypassing the bias. Issue 5 (1st October 2021) - Burrell, Angeline G; Jones, McArthur; Halford, Alexa; Zawdie, Kate; Coxon, John
Abstract : Angeline G Burrell, McArthur Jones Jr, Alexa Halford, Kate Zawdie and John Coxon have collaborated to create a set of tools to tackle conscious and unconscious bias in space physics research Abstract: Angeline G Burrell, McArthur Jones Jr, Alexa Halford, Kate Zawdie and John Coxon have collaborated to create a set of tools to tackle conscious and unconscious bias in space physics research